Indonesian Students’ Prejudice Against Homosexuals: Religious Fundamentalism and Intergroup Threat as Predictors - Chandra, Jessica; Sampe Tondok, Marselius; Balgies, Soffy (Bina Nusantara University, 2022)
The research aimed to examine and explain the relationship between religious fundamentalism and intergroup threats toward undergraduate students’ prejudice against gays and lesbians. Bhinneka Tunggal Ika, a slogan about tolerance, is supposed to protect and enhance diversity in Indonesia. On the contrary, sexual minority groups, gays and lesbians, often accept stereotypes, prejudices, and discrimination from the majority of Indonesian because they are considered against the religious values and morality of Indonesian. The research used a cross-sectional survey design with accidental sampling methods. The research subjects were students aged 18 to 24 years who studied at universities in Surabaya, identified as heterosexuals, and with diverse religious backgrounds (N = 414). The instruments used were the Attitudes Towards Lesbians and Gay Men (ATLG), the Revised Religious Fundamentalism Scale (RFS-12), and the Perceived Threat of Homosexuals (PTHS) Scale. Multiple regression analysis shows that religious fundamentalism and intergroup threat plays a significant role in explaining prejudice against gays and lesbians (R = 0,872; R² = 0,761; F = 654,817; p < 0,001). The role of intergroup threat as a predictor of prejudice against gays and lesbians is higher than religious fundamentalism.Additional analysis shows that academic discipline, contact, empathy, religion, and university characteristics affect students’ prejudice.